Benign and Suspicious Ovarian Masses—MR Imaging Criteria for Characterization: Pictorial Review. (22nd March 2012) - Valentini, A. L.; Gui, B.; Miccò, M.; Mingote, M. C.; De Gaetano, A. M.; Ninivaggi, V.; Bonomo, L.
Abstract : Ovarian masses present a special diagnostic challenge when imaging findings cannot be categorized into benign or malignant pathology. Ultrasonography (US), Computed Tomography (CT), and Magnetic Resonance Imaging (MRI) are currently used to evaluate ovarian tumors. US is the first-line imaging investigation for suspected adnexal masses. Color Doppler US helps the diagnosis identifying vascularized components within the mass. CT is commonly performed in preoperative evaluation of a suspected ovarian malignancy, but it exposes patients to radiation. When US findings are nondiagnostic or equivocal, MRI can be a valuable problem solving tool, useful to give also surgical planning information. MRI is well known to provide accurate information about hemorrhage, fat, and collagen. It is able to identify different types of tissue contained in pelvic masses, distinguishing benign from malignant ovarian tumors. The knowledge of clinical syndromes and MRI features of these conditions is crucial in establishing an accurate diagnosis and determining appropriate treatment. The purpose of this paper is to illustrate MRI findings in neoplastic and non-neoplastic ovarian masses, which were assessed into three groups: cystic, solid, and solid/cystic lesions. MRI criteria for the correct diagnosis and characteristics for differentiating benign from malignant conditions are shown in this paper.